Effects of vesicular-arbuscular mycorrhizae on the growth and uptake of some heavy metals by oat - Rakshit, Amitava; Choudhury, A.; Bhadoria, P.B.S (MTT, 2004)
Today, agriculture practices by taking environmental concerns into account are of great importance. This has urged consistent cultivation and production systems to be developed and implemented. The purpose of the agriecosystem is to ensure alternatives with the concern that population of natural species is to be sustained and the likelihood hazardous effects is to be minimized. One of these alternatives is use of soil microorganisms in agriculture (Weissenhorn at al. 1995), specifically mycorrhizal fungi which can be of great importance in heavy metal availability and toxicity (Leyval at al. 1997). Thereby a natural protection management might be promoted. The objective was to investigate the possibilities of utilisation of VAM in mitigating pollution in soil. Uptake of heavy metals by plants, the effects of mycorrhiza on heavy metal absorbed by plants and mycorrhizal tolerance to heavy metals were explained. Soil samples were taken from farmers field at the depth of 0-20 cm. The sieved soil was mixed with sand (3:1) and was sterilised. Oat roots were inoculated with four species of VAM fungus and the rate of infection on the roots was determined, the test plants was local variety of oat. The different metal contents in the soil were obtained by adding aqueous solutions of ZnSO4. 7H2O ,Cu SO4. 5H2O and 3Cd(SO4). 8H2O . All treatments were applied with and without mycorrhizal inoculum and there were four replicates. Heavy metal contents increased in soil, root, stem and leaves, depending on the increased doses of Cu, Zn and Cd in both inoculated and noninoculated treatments. Infection rate was found 36 % in VAM infected oat roots. As a result of increased heavy metal application (Cu, Zn and Cd) VAM infection rate lessened [ Cu (36-21%), Zn (36-15%) and Cd (36-4%)]. Large part of the metals were retained by roots (Gildon & Tinker1983) VA mycorrhiza hindered metal movements to stem and leaves. (Graham & Fardelman 1986). The filtering property of mycorrhiza may contribute to the efforts to mitigate high levels of heavy metals in soils. Gildon, A & Tinker P.B. 1983. New Phytologist, 95: 247-261. Graham, J.H. & Fardelmann, D.1986. Canadian Journal of Botany 64:1739-1744. Leyval, C. et al. 1997. Mycorrhiza 7(3): 139-153. Weissenhorn, I. et al. 1995. Mycorrhiza 5: 245-251.
Keywords: Ka; vesicular-arbuscular mycorrhizae; growth; uptake; heavy metals